2017
DOI: 10.1016/j.euroneuro.2017.07.001
|View full text |Cite
|
Sign up to set email alerts
|

International trends in antipsychotic use: A study in 16 countries, 2005–2014

Abstract: The objective of this study was to assess international trends in antipsychotic use, using a standardised methodology. A repeated cross-sectional design was applied to data extracts from the years 2005 to 2014 from 16 countries worldwide. During the study period, the overall prevalence of antipsychotic use increased in 10 of the 16 studied countries. In 2014, the overall prevalence of antipsychotic use was highest in Taiwan (78.2/1000 persons), and lowest in Colombia (3.2/1000). In children and adolescents (0-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
189
3
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 210 publications
(212 citation statements)
references
References 55 publications
16
189
3
4
Order By: Relevance
“…However, there is significant variation in the evidence of efficacy for the treatment of these conditions . The overall prevalence of antipsychotic use has been increasing, and population studies have found the use of antipsychotic drugs in non‐psychotic disorders such as depression, anxiety, autism spectrum disorders to be common . In Norway, increasing use of the second‐generation antipsychotic quetiapine was found to coincide with decreasing mean doses and increased prescribing for non‐psychotic disorders, indicating increasing off‐label use .…”
Section: Introductionmentioning
confidence: 99%
“…However, there is significant variation in the evidence of efficacy for the treatment of these conditions . The overall prevalence of antipsychotic use has been increasing, and population studies have found the use of antipsychotic drugs in non‐psychotic disorders such as depression, anxiety, autism spectrum disorders to be common . In Norway, increasing use of the second‐generation antipsychotic quetiapine was found to coincide with decreasing mean doses and increased prescribing for non‐psychotic disorders, indicating increasing off‐label use .…”
Section: Introductionmentioning
confidence: 99%
“…Sufficient data were present only for weight changes in case of olanzapine and risperidone. Latest pharmacoepidemiological data report that olanzapine and risperidone are across the three most prescribed AP and, therefore, the presented findings represent a predominant group of patients using AP . Thus, the role of sex has not been explicitly addressed in sufficient detail in a sufficient number of studies hampering definitive conclusions.…”
Section: Discussionmentioning
confidence: 55%
“…Following the policy change, we observed a sustained increase in the rate of 25-mg quetiapine dispensing by 11/month (95% CI: [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] and all other quetiapine strengths combined by 14/month (95% CI: [8][9][10][11][12][13][14][15][16][17][18][19][20]. We did not observe a monthly increase in dispensing rate (ramp) for all antipsychotics minus quetiapine, but there was a step increase of 2162 (95% CI: 773-1371) dispensings that occurred gradually over the study period (Table 2).…”
Section: Dispensingsmentioning
confidence: 99%
“…Quetiapine is a short acting antipsychotic available in immediate and extended release formulations, with level 1 evidence to support its use in treating schizophrenia and bipolar I disorder . Since its initial listing for public subsidy in Australia in 2000, quetiapine has become the most frequently dispensed antipsychotic in Australia and many other countries …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation